THE STUDY OF STUDENTS’ DIFFICULTY IN OPERATING OBE THROUGH TPS METHOD: A CASE STUDY OF ALE (ELEMENTARY LINEAR ALGEBRA) COURSE - *, Fauziah; Wahyuni, Yusri (IJRDO- Journal of Educational Research, 2017)
This study aims to assess and analyze the students’ results of learning OBE Elementary LinearAlgebra (ALE) using Think Pair Share learning model. This study was a classroom action research for thisstudy aims to improve the learning outcomes of students who take mathematics education especially ElementaryLinear Algebra course and improvements made continuously during the research.Subject of this study are 41students of class A Faculty of Mathematics Education and Teaching who take Elementary Linear Algebracourse in second semester of academic year 2015/2016. Data were analyzed by using simple statistics. Based onthe analysis of the data, the study concluded that the learning outcomes of students increased from the firstcycle to the second cycle and reach the target of this study is 70% that most of students in the class scored ≥ B.